The Gender Recontest Gap in Elections - Thushyanthan Baskaran; Zohal Hessami (Institute of Labor Economics (IZA), 2021)
This paper documents an important but mostly overlooked reason for female underrepresentation in politics: gender gaps in the recontest likelihood of candidates. Using hand-collected data on 116,185 candidates in four consecutive local council elections (2001-2016) in a German state, we provide evidence for a gender recontest gap among both incumbent and non-incumbent candidates. Female candidates are 4 to 5 percentage points less likely than male candidates to run again conditional on previous candidacy. Studying mechanisms, we find that women are likely held back by incompatibilities between family obligations and political duties as well as a culture of male dominance in local politics.
Keywords: D72; D78; J16; 330; gender; political selection; persistence; local councils; candidacy